1981
DOI: 10.1212/wnl.31.10.1323
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic hypotension in familial amyloid polyneuropathy

Abstract: We measured plasma norepinephrine levels in patients with familial amyloid polyneuropathy. Patients with orthostatic hypotension had low basal plasma norepinephrine levels, which did not increase after postural change. On the basis of biochemical findings that suggest depletion of peripheral norepinephrine, DL-threo-3,4-dihydroxyphenylserine, an immediate precursor of norepinephrine, was given orally. Six hundred mg of this drug induced substantial and sustained elevation of blood pressure for several hours, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Orthostatic hypotension is a common cardiovascular manifestation of autonomic dysfunctions in FAP2 and results from impaired baroreflex and cardiac dysfunctions 43, 44. FAP patients with orthostatic hypotension had low basal plasma norepinephrine levels, which did not increase after postural change 45. Pathological and imaging studies showed neuronal cell loss in sympathetic ganglia and reduction of myocardial MIBG uptake in FAP 30, 46.…”
Section: Discussionmentioning
confidence: 99%
“…Orthostatic hypotension is a common cardiovascular manifestation of autonomic dysfunctions in FAP2 and results from impaired baroreflex and cardiac dysfunctions 43, 44. FAP patients with orthostatic hypotension had low basal plasma norepinephrine levels, which did not increase after postural change 45. Pathological and imaging studies showed neuronal cell loss in sympathetic ganglia and reduction of myocardial MIBG uptake in FAP 30, 46.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of autonomic nervous system is striking: constipation, explosive diarrhea, sexual impotence, sphincter impairment, hypohidrosis, orthostatic hypotension, and disordered cardiac conduction. In previous studies, we found that patients with advanced FAP had decreased urinary excretion rates of norepinephrine (NE) (Suzuki et al, 1979) 24 T. Azuma et al and a low level of plasma NE concentration (Suzuki et al, 1981), and that the responsiveness of their blood pressure to infused NE was exaggerated (Suzuki et al, 1980). We suggested that in advanced FAP patients noradrenergic receptors are more sensitive to agonists because NE in the sympathetic nerves is chronically depleted.…”
Section: Introductionmentioning
confidence: 99%
“…Orthostatic hypotension (OH) is one of the major complications in many neurological disorders such as Parkinson’ disease (PD) [1, 2], multiple system atrophy (MSA) [2, 3], diabetic neuropathy [4, 5], and familial amyloid polyneuropathy (FAP) [6, 7]. Symptoms suggestive of OH range from mild dizziness on standing to syncopal collapse, and potentially at least, to cerebral hypoperfusion, thrombotic stroke, and possibly, myocardial infarction, and so they often restrict these patients’ daily lives [8].…”
Section: Introductionmentioning
confidence: 99%